One minute mother - "Johnson, Spencer" (New York, 1983)
The One Minute Mother's symbol- a one-minute readout from the face of a modern digital watch- is intended to remind each of us to take a minute out of our day, every now and then, and look into the faces of our children.
Keywords: Psychology Applied